Efectividad de los Programas de Rehabilitación en el Sistema Penitenciario Ecuatoriano - Paladines Alulima, Melissa Carolina (2024)
This thesis focuses on assessing the effectiveness of the rehabilitation programs implemented within the Ecuadorian prison system. The research examines how these programs have been structured and applied, their impact on reducing criminal recidivism, and the main challenges they face. The study begins with a detailed analysis of the historical and legal context shaping rehabilitation programs in Ecuador. It examines the legal foundations established by the 2008 Constitution and the Organic Comprehensive Criminal Code (COIP), and reviews the historical evolution of these programs to understand their development over time. It then examines the essential features of the rehabilitation programs, including education and job training, psychological treatment, and recreational and cultural activities. The analysis investigates how these elements are designed to meet the needs of inmates and their role in promoting effective rehabilitation. Through surveys and interviews with prison staff and field experts, the study reveals that, despite significant efforts by the government and involved institutions, the current rehabilitation programs have not proven effective in their current state. The data indicates that there has not been a significant reduction in recidivism or successful reintegration of inmates into society The thesis identifies and examines the primary challenges and limitations affecting program effectiveness, such as inadequate resources, insufficient trained personnel, and difficulties in program monitoring and evaluation. Additionally, it looks at opportunities to improve program implementation, focusing on strategies to optimize resource use and develop specialized staff. Finally, the study reviews the impact of various penitentiary regimes on rehabilitation and assesses the role of penitentiary rehabilitation within Ecuador's constitutional framework. This analysis provides a comprehensive view of the current issues and offers recommendations for future improvements in the Ecuadorian prison rehabilitation system. Keywords: Penitentiary rehabilitation, Ecuadorian penitentiary system, program effectiveness, education and vocational training, psychological treatment, recreational and cultural activities, legal framework, Constitution, Organic Comprehensive Criminal Code, challenges and limitations, resources and trained personnel, social reintegration, types of penitentiary regimes,